Outcomes in Patients with Left Ventricular Assist Devices, Pacemakers, and Implantable Cardioverter Defibrillators Undergoing Single Balloon Enteroscopy. Issue 2 (February 2019) - Patel, Brijesh; Shiani, Ashok; Rodriguez, Andrea C.; Lipka, Seth; Davis-Yadley, Ashley H.; Nelson, Kirbylee K.; Rabbanifard, Roshanak; Kumar, Ambuj; Brady, Patrick G.
Abstract : Objectives: Obscure overt gastrointestinal bleeding can be challenging to evaluate in patients with electronic cardiac devices such as continuous flow left ventricular assist devices (LVADs), pacemakers (PPMs), and implantable cardioverter defibrillators (ICDs). Limited data exist on the utility and safety of single balloon enteroscopy (SBE) in patients with cardiac devices. We aimed to evaluate the safety, efficacy, diagnostic, and therapeutic outcomes of the aforementioned devices in patients undergoing SBE. Methods: A retrospective study was performed using the medical records of 57 patients undergoing SBE at our institution from 2010 to 2014. Patients were divided into two groups: those with cardiac devices and those without. Data on comorbidities, complications, findings, diagnostic, and therapeutic yield were compared. t Test and logistic regression assessed the association between dependent and independent variables. For continuous data, the results were summarized as mean difference and standard deviation. For dichotomous data, the results were summarized as odds ratio and 95% confidence intervals. Results: The overall age in patients with cardiac devices was 67.89 ± 6.96 versus 66.03 ± 11.95 years in the control. The cardiac device group was composed of 42.1% women; the control comprised 21.1% women. There were 19 patients with cardiac devices; 8 (LVAD + ICD), 1 (LVAD + PPM + ICD), 2 (PPM + ICD), 6 (PPM), 2 (ICD); 38 patients were in the control group. Patients with cardiac devices were hospitalized more often than patients without devices; this finding was not statistically significant (odds ratio 1.826, 95% confidence interval 0.544–6.128, P = 0.389). Procedure times were longer in the cardiac device group, 65.16 ± 49.92 minutes, when compared with the control, 57.40 ± 20.42, but it also did not reach statistical significance (mean difference 7.758, 95% confidence interval −11.360 to 26.876, P = 0.049). There was no statistically significant difference in major or minor events between patients with cardiac devices and the control group. Diagnostic and therapeutic yield and rebleeding rates were similar across both groups. Conclusions: Patients in the cardiac device group did not appear to be at any more significant risk than those without cardiac devices. Furthermore, diagnostic and therapeutic yield and rebleeding rates appear to be similar across both groups. Clinicians may perform SBE in these patients safely and effectively, with good overall outcomes. Abstract : The authors evaluated the safety, efficacy, and diagnostic and therapeutic yields of balloon-assisted enteroscopy in patients with continuous-flow left ventricular assist devices, pacemakers, and implantable cardioverter defibrillators who presents with obscure gastrointestinal bleeding. They evaluated safety and efficacy in cardiac patients who already have significant comorbidities from the cardiac standpoint and their risk for undergoing small bowel enteroscopy.